2017
DOI: 10.1038/srep45150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of decomposition and organic residues on resistivity of copper films fabricated via low-temperature sintering of complex particle mixed dispersions

Abstract: Mixtures of a copper complex and copper fine particles as copper-based metal-organic decomposition (MOD) dispersions have been demonstrated to be effective for low-temperature sintering of conductive copper film. However, the copper particle size effect on decomposition process of the dispersion during heating and the effect of organic residues on the resistivity have not been studied. In this study, the decomposition process of dispersions containing mixtures of a copper complex and copper particles with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
(62 reference statements)
0
23
0
Order By: Relevance
“…Yonezawa et al . reported that a small amount of low-molecular-weight gelatin on a Cu 2 O layer on the surface of copper NPs prevented further oxidation of the copper NPs 36 . Based on our results, the NTA on the surface of the copper NPs also prevents oxidation of the copper NPs in the present study.
Figure 1Crystal structure analysis and morphological observation of copper NPs.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yonezawa et al . reported that a small amount of low-molecular-weight gelatin on a Cu 2 O layer on the surface of copper NPs prevented further oxidation of the copper NPs 36 . Based on our results, the NTA on the surface of the copper NPs also prevents oxidation of the copper NPs in the present study.
Figure 1Crystal structure analysis and morphological observation of copper NPs.
…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, studies utilizing inexpensive copper as nanoinks for circuit-forming materials and bonding materials instead of silver nanoparticles have expanded 3034 because the thermal conductivity of bulk copper is 398 W·m −1 ·K −1 . To date, various methods, such as hydrazine reduction 2,35,36 , polyol reduction 3741 , thermal decomposition 42 , and electrochemical reduction 30 , have been proposed for the synthesis of copper nanoparticles (NPs) with low-temperature sintering ability. Despite extensive efforts by researchers, the above-mentioned methods require the use of polymers and surfactants to control the diameter of copper NPs and prevent aggregation in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…As for other methods, it has been reported that by sintering a mixture of copper particles and copper-based metal-organic decomposition ink, a highly conductive sintered copper film could be obtained at a sintering temperature of 100°C. 88,89)…”
Section: A D V a N C E V I E Wmentioning
confidence: 99%
“…H 2 or vaporized formic acid) or inert gas (e.g. N 2 ) to produce the conductive patterns because the air-thermal sintering process of Cu-based inks tends to oxidize the copper [1232]. The development of air-sintered Cu-based inks compatible with quick and effective roll-to-roll processes in printable electronics would represent a substantial advancement.…”
Section: Introductionmentioning
confidence: 99%